Catalytic Ozonation of Phenolic Wastewater: Identification and Toxicity of Intermediates - Mahdi Farzadkia; Yousef Dadban Shahamat; Simin Nasseri; Amir Hossein Mahvi; Mitra Gholami; Ali Shahryari (Journal of Engineering)
A new strategy in catalytic ozonation removal method for degradation and detoxification of phenol from industrial wastewater was investigated. Magnetic carbon nanocomposite, as a novel catalyst, was synthesized and then used in the catalytic ozonation process (COP) and the effects of operational conditions such as initial pH, reaction time, and initial concentration of phenol on the degradation efficiency and the toxicity assay have been investigated. The results showed that the highest catalytic potential was achieved at optimal neutral pH and the removal efficiency of phenol and COD is 98.5% and 69.8%, respectively. First-order modeling demonstrated that the reactions were dependent on the initial concentration of phenol, with kinetic constants varying from 0.038 min−1  ([phenol]o = 1500 mg/L) to 1.273 min−1 ([phenol]o = 50 mg/L). Bioassay analysis showed that phenol was highly toxic to Daphnia magna (LC50 96 h=5.6 mg/L). Comparison of toxicity units (TU) of row wastewater (36.01) and the treated effluent showed that TU value, after slightly increasing in the first steps of ozonation for construction of more toxic intermediates, severely reduced at the end of reaction (2.23). Thus, COP was able to effectively remove the toxicity of intermediates which were formed during the chemical oxidation of phenolic wastewaters.